Ischemia of Non-Obstructive Coronary Artery Disease: Need to Address in our Patient Population - Islam, AHM Waliul; Reza, AQM; Munwar, Shams; Talukder, Shahabuddin; Ahmed, Tamzeed; Rahman, Kazi Atikur; Ali, Md Atahar (Cardiovascular Journal, 2021)
Ischemia of non-occlusive coronary artery disease (INOCA) not an uncommon phenomenon, exist in our patient population which did not address well. Many of the stable angina and or unstable angina patient, whose coronary angiogram revealed significant coronary stenosis (>70%) are being treated by PCI with drug eluting stent. On the contrary, quite a significant proportion of patient, who are found to have non-significant coronary lesion (<50%) or essentially normal epicardial coronaries. These group of patients with angiographic evidence of non-occlusive CAD, remain undiagnosed of their exact etiology of angina. As a result, recurrence of anginal chest pain leading to repeat hospitalization impaired quality of life and the expenditure. Women are significant number in this category, labelled as syndrome X. Many of the scientific literature, has labeled it as Ischemia of Non obstructive Coronary artery Disease. Notably, Microvascular angina is due to ischemia driven mismatch of demand and supply in the myocardium. Microvascular Dysfunction (MVD) and Coronary vascular spasm or Vasospastic Angina (VSA) are the main pathogenic causes of INOCA. With the advent of Imaging physiology, and its availability in Bangladesh, many of the center can assess INOCA and its severity by FFR, iFR, DFR and transthoracic Doppler study of the coronaries. Therefore, we recommend evaluating INOCA patient by available technical assistance and to address the issue and patients suffering with repeated hospitalization and financial expenditure. Cardiovasc. j. 2021; 13(2): 217-222